2001
DOI: 10.1080/108712001753473939
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Specialization Index and Testing of Specialization Theory

Abstract: Recreation specialization can be viewed as a continuum of behavior from the general to the particular. Along this continuum, participants can be located into meaningful subgroups based on specific criteria. Previous studies have defined, measured, and segmented specialization groups in a variety of ways. The research reported here builds on the Ditton, Loomis, and Choi reconceptualization of recreation specialization. A specialization index was developed to segment anglers into four groups based on their orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
73
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 22 publications
2
73
1
1
Order By: Relevance
“…An understanding of different specialization levels is useful to resource management in that it allows managers to distinguish between different interests and preferences among resources users when making resource allocation decisions. From a 1998 survey of licensed Massachusetts anglers, Salz et al (2001) developed three subgroups of anglers based on their activity orientation, experiences, relationships, and commitment. Results from the 2001 study showed strong support for specialization theory, and suggested that managers consider differences in these three groups when making resource allocation decisions.…”
Section: Proceedings Of the 2003 Northeastern Recreation Research Symmentioning
confidence: 99%
See 4 more Smart Citations
“…An understanding of different specialization levels is useful to resource management in that it allows managers to distinguish between different interests and preferences among resources users when making resource allocation decisions. From a 1998 survey of licensed Massachusetts anglers, Salz et al (2001) developed three subgroups of anglers based on their activity orientation, experiences, relationships, and commitment. Results from the 2001 study showed strong support for specialization theory, and suggested that managers consider differences in these three groups when making resource allocation decisions.…”
Section: Proceedings Of the 2003 Northeastern Recreation Research Symmentioning
confidence: 99%
“…Building on the work of Ditton et al (1992), Salz et al (2001) developed a multi-item specialization index using the social subworlds concept of Unruh (1979). Specifically, the authors used four variables to determine specialization level: orientation, experiences, relationships, and commitment.…”
Section: Proceedings Of the 2003 Northeastern Recreation Research Symmentioning
confidence: 99%
See 3 more Smart Citations